Determination of T-2 toxin in grain and grain products by HPLC and TLC - (:unkn) unknown (TAYLOR & FRANCIS INC, 2000)
The purpose of this study was to investigate the T-2 toxin contaminated grain and grain products consumed especially by Turkish population. The T-2 toxin was detected using the high performance liquid chromatography (HPLC) with UV detector at 208 nm and the identify of T-2 was further confirmed by thin layer chromatography (TLC). The recovery was 91+/-4.24% for corn flour fortified with the known amount of T-2 toxin (1 ppm). The detection limits of T-2 toxin for the HPLC and the TLC were 25 ng and 50 ng, respectively A total of 30 commercially available grain and grain product samples were analyzed. Two corn flour samples were found to contain detectable levels of T-2 toxin at a level of 1.60 ppm and 4.08 ppm.
Keywords: T-2 toxin; grain and grain products; HPLC; TLC; PERFORMANCE LIQUID-CHROMATOGRAPHY; TRICHOTHECENE MYCOTOXINS; MASS-SPECTROMETRY; SCREENING METHOD; MYCO-TOXINS; METABOLITES; LAYER